Alternatif Selective Breeding (Seleksi Induk/Calon Induk Ikan) Untuk Meningkatkan Jumlah Dan Kualitas Induk/Calon Induk Ikan Lele - Abi Fahrurrazi; Ersa Tri Fitriasari (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
This study aims to increase the distribution of catfish to the community and groups, increase the number and improve the quality of broodstock/prospective broodstock of catfish through selective breeding. The stages of selective breeding (selection of broodstock/prospective broodstock fish), resulted an increase in the number and quality improvement of broodstock/prospective broodstock catfish through family selection and individual selection, increasing quality catfish, and increasing the distribution of catfish to communities and groups. With the process of selective breeding stages, the availability of basic instructions in brood management for BBIAT Pampang officers, as well as increasing quality broodstock/prospective broodstock so as to increase catfish seed production and can meet the needs of the people of North Kayong Regency.